Analisis Kandungan Kimia Biskuit Umbi Are atau Gadung (Dioscorea hispida) Asal Kabupaten Alor - Hemy R. Djasibani; Anita T. Dimu Lobo; Elia Padaakani (Peneliti.net, 2021)
Gadung or yam “are” or (Dioscorea hispida) is a plant belonging to tubers that thrives in the tropics. Biscuits are products obtained by baking dough derived from wheat flour with the addition of other foods and with or the addition of permitted food additives. This study aims to determine the content and amount of biscuits. The design used in this study was a completely randomized design (CRD) with 4 treatments and 3 replications. Parameters observed were water content, protein content and carbohydrate content. Biscuits produced from each treatment contain water content, protein content, carbohydrate content. The moisture content of the biscuits in treatments B, C, and D still met the quality requirements of SNI 01-2973-2011, namely a maximum of 5, the protein content of biscuits in treatments A, B and C still met the quality requirements of SNI 01-2973-2011, namely a minimum of 5 and Carbohydrate levels in each treatment were very high, namely A (48.03), B (47.68), C (49.69) and D (56.64).